PENGARUH EARNING PER SHARE, RETURN ON INVESTMENT, TERHADAP RETURN SAHAM PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - ZAKIA FADILA,; MARDIAH HASANAH (JURNAL ILMIAH KOHESI, 2020)
This study aims to examine the influence of Earning Per Share, Return On Investment on stock returns. Independent variables in this study are Earning Per Share, Return On Investment and while the dependent variable is stock return. The population in this study as many as 49 property and real estate companies listed on the Indonesia Stock Exchange period 2015-2019. The sample was taken using purposive sampling technique and obtained 15 companies that made the sample. This research uses quantitative research approach, descriptive research type, explorative research nature, and secondary data source. Data collection technique was done by observation and data analysis using multiple linear analysis using F test and t test at 5% significant level (α = 0,05) and R Square (R2) determination coefficient 0,133 which mean 13,3% changes in stock return variables (Y) are explained by changes in Earning Per Share (X1), Return On Investment (X2), and (X3), while the remaining 86.7% is explained by other un-researched variables. The results of this study indicate that simultaneously Earning Per Share, Return On Investment, and does not affect the stock return, while partially Retrun On Investment has no significant effect on stock returns and partially Earning Per Share and no significant effect against stock returns on property and real estate firms listed on the Indonesia Stock Exchange period 2015-2019.